OP0239 What constitutes the characteristic fat lesion on MRI of the sacroiliac joints in early spondyloarthritis?. (23rd January 2014) - Weber, U.; Pedersen, S.J.; Zubler, V.; Rufibach, K.; Chan, S.; Lambert, R.G.; Ostergaard, M.; Maksymowych, W.P.
Abstract : Background: It is well known that fat infiltration (FI) of bone marrow may be observed on T1-weighted MRI in the sacroiliac joints (SIJ) of both healthy individuals and patients with spondyloarthritis (SpA). But it is unclear whether the MRI features of FI allow characterization of FI as pathological rather than physiological. Moreover, it is unclear if this might have diagnostic utility in early SpA. Objectives: To assess which MRI features of fat contribute to diagnostic utility of SIJ MRI in 2 inception cohorts of early SpA. Methods: Cohort A comprised 69 consecutive patients ≤50 years referred from primary care and rheumatology practices for assessment of back pain, cohort B comprised 88 consecutive patients ≤50 years with acute anterior uveitis and back pain. They were classified according to clinical examination and pelvic X-ray as having non-radiographic axial SpA (nr-axSpA) (n=20 and 31 for cohorts A and B, respectively), ankylosing spondylitis (AS) (n=10 and 24), or mechanical back pain (MBP) (n=39 and 33). Cohort A also comprised 20 healthy volunteers (HV). SIJ MRI were assessed independently in random order by 4 blinded readers for the following morphological features of FI: distinct border around the region of FI, homogeneity of the T1W signal, proximity to subchondral bone, and association with other SIJ lesions (bone marrow edema, erosion). Results: FI of the SIJ in cohort A and B was recorded by the majority (≥3/4) of readers in AS in 60% and 73.9%, in nr-axSpA in 40% and 38.7%, in MBP in 20.5% and 12.1%, respectively, and in HV in 10%. Diagnostic utility (mean of 4 readers for cohort A/B) of SIJ FI in nr-axSpA vs MBP patients: Conclusions: FI characterized by a distinct border or homogeneity on SIJ MRI had substantial diagnostic utility in early SpA. FI in combination with BME or ER also showed high diagnostic utility. Disclosure of Interest: None Declared